2006
DOI: 10.2106/jbjs.e.00333
|View full text |Cite
|
Sign up to set email alerts
|

Functional Significance of Bone Density Measurements in Children with Osteogenesis Imperfecta

Abstract: There is a relationship between bone mineral density and the functional outcome, rate of fracture, and rate of surgery in patients with osteogenesis imperfecta. Bone mineral density appears to be an indicator of disease severity and may be predictive of long-term functional outcome. To establish specific guidelines for treatment, more data on normative bone-mineral density in children with osteogenesis imperfecta will be needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 25 publications
1
14
1
1
Order By: Relevance
“…They are present in up to 60% of affected children • Protrusio acetabuli, in which the socket of the hip joint is too deep and the acetabulum bulges into the cavity of the pelvis causing intrapelvic protrusion of the acetabulum • Low bone density detected by dual energy x-ray absorptiometry (DEXA). There seems to be a correlation between BMD and fracture risk in OI 34,35 Note:…”
Section: Establishing a Diagnosismentioning
confidence: 99%
“…They are present in up to 60% of affected children • Protrusio acetabuli, in which the socket of the hip joint is too deep and the acetabulum bulges into the cavity of the pelvis causing intrapelvic protrusion of the acetabulum • Low bone density detected by dual energy x-ray absorptiometry (DEXA). There seems to be a correlation between BMD and fracture risk in OI 34,35 Note:…”
Section: Establishing a Diagnosismentioning
confidence: 99%
“…Often, children with type I OI are overlooked for therapeutic intervention during times of nonfracture due to their relatively high functional abilities and normal appearance in comparison to more severe types of OI. The broad range of variability of expression in this disease has been characterized in the past using various functional assessment tools such as the Pediatric Evaluation of Disability Inventory, 14-17 the SF-36 health self-assessment questionnaire, 18 the Pediatric Outcomes Data Collection Instrument (PODCI), 19 the Gross Motor Function Measure, 17 the Brief Assessment of Motor Function, 20 bone densitometry, 10,12,17,19 ambulation level, muscle force, and joint range of motion measurements. 12,16,19,21 Several functional assessment and mobility development studies have grouped all types of OI together.…”
Section: Interventionmentioning
confidence: 99%
“…12,16,19,21 Several functional assessment and mobility development studies have grouped all types of OI together. 19 However, OI is a heterogeneous group that is best analyzed in subgroups to draw more specific conclusions about care. The aim of this study was to improve the evaluation process of children with type I OI by providing a quantitative comparison of gait and selected functional assessments to age-matched controls.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomized and controlled trials have also shown reductions in fracture rates and bone pain in some cases [21][22][23][24]. However, these findings are not universal [25], and not necessarily linked to a better quality of life [26], although BMD has been considered a guide to functional outcome [27]. Further studies are needed to confirm the reduction in long bone fracture incidence [28]-a difficult undertaking considering the rarity of this condition.…”
Section: Introductionmentioning
confidence: 99%